Gold-catalyzed highly selective photoredox C(sp2)-H difluoroalkylation and perfluoroalkylation of hydrazones - Xie, Jin; Zhang, Tuo; Chen, Fei; Mehrkens, Nina; Rominger, Frank; Rudolph, Matthias; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2016)
The first gold-catalyzed photoredox C(sp2)-H difluoroalkylation and perfluoroalkylation of hydrazones with readily available RF-Br reagents is reported. The resulting gem-difluoromethylated and perfluoroalkylated hydrazones are highly functionalized, versatile molecules. A mild reduction of the coupling products can efficiently produce gem-difluoromethylated β-amino phosphonic acids and β-amino acid derivatives. In mechanistic studies, a difluoroalkyl radical intermediate was detected by an EPR spin-trapping experiment, indicating that a gold-catalyzed radical pathway is operating.
Gesehen am 29.09.2017
Im Titel ist "2" hochgestellt